A novel muscle cramp scale (MCS) in amyotrophic lateral sclerosis (ALS). Issue 5 (3rd July 2019) - Mitsumoto, Hiroshi; Chiuzan, Codruta; Gilmore, Madison; Zhang, Yuan; Ibagon, Camila; McHale, Brittany; Hupf, Jonathan; Oskarsson, BjÖrn
Abstract: Objective: To develop a novel muscle cramp scale (MCS) to assess frequency, severity and clinically meaningful information related to cramps among patients with amyotrophic lateral sclerosis (ALS). Methods: This new scale comprises four 5-point subdomains: (1) triggering factors, (2) frequency, (3) location, (4) severity, and (5) the degree to which cramps affect overall daily living. Thirty patients with ALS, who experienced at least 5 cramps per week, participated in a randomized test-retest study. An additional 26 patients participated in a second study assessing cramp changes over 4 weeks using the MCS and a detailed cramp diary. Results: To establish internal reliability of the scale, a Cronbach's coefficient value of 0.75 or higher was considered acceptable. Test/retest evaluations comparing in-person and telephone administration were assessed using paired t -tests and Cohen's kappa statistics. Non-significant differences were identified, and the results revealed moderate to high agreement for each item (range 0.60 to 0.95, p  < 0.0001). Scale construct validity against the cramp diary was acceptable. There were essentially no significant mean differences in muscle cramps over 4 weeks measured using the MCS and diary, respectively. Conclusions: The MCS is a valid, simple, and quick measure for the assessment of muscle cramps in patients with ALS. It can be reliably administered either in person or by telephone and provides richer information than the routinely utilized cramp diary.